How Speech–Language Pathologists Adapt This Is Me Digital Transition Portfolios to Support Individuals with Intellectual/Developmental Disabilities and Communication Challenges Across Settings - Eve Müller; Jamie R. Kleiner; Danielle Evans; Ann Kern; Dawn Reikowsky; Katherine Smidl (Education Sciences)
Critical information is frequently lost when individuals with intellectual/developmental disabilities (I/DD) and co-occurring communication challenges transition from one educational/clinical setting to another. To encourage a seamless transition, speech–language pathologists (SLPs) developed This is Me (TiME), a customizable, digital transition tool designed to help students/patients share personal information and advocate for needed support in their new settings. Researchers conducted a content analysis of 92 TiME transcripts to determine how SLPs used the tool across school and inpatient contexts. Findings indicate the most common content domains included in TiME were personal information (e.g., strengths, hobbies, and preferences) and information about communication, learning styles, and behavior/emotion regulation. While school and inpatient units demonstrated similar patterns of domain use, TiME created in an inpatient context contained more information about behavior plans/supports and were almost twice as long on average. They also included more information about safety and diagnoses/medical needs and less information about self-advocacy strategies than TiME created in school contexts, reflecting the very different settings within which they were created. These findings suggest that TiME offers a solution that can readily be adapted to meet the needs of varied groups of individuals with disabilities as well as different audiences.